2016
DOI: 10.1016/j.jvs.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Number of infrapopliteal arteries undergoing endovascular treatment is not associated with the limb salvage rate in patients with critical limb ischemia

Abstract: Our results suggest that it is not necessary to treat the largest number of arteries possible in CLI patients. Instead, the most amenable artery for endovascular procedures should be treated to improve limb salvage and secondary patency rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
(21 reference statements)
0
13
1
Order By: Relevance
“…These findings differ from those of a previous study undertaken in our department, in which de Athayde Soares et al. 11 investigated whether the number of infrapopliteal arteries undergoing endovascular treatment was associated with the limb salvage rate in patients with critical limb ischemia. The conclusion drawn was that it is not necessary to treat the largest number of arteries possible in these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings differ from those of a previous study undertaken in our department, in which de Athayde Soares et al. 11 investigated whether the number of infrapopliteal arteries undergoing endovascular treatment was associated with the limb salvage rate in patients with critical limb ischemia. The conclusion drawn was that it is not necessary to treat the largest number of arteries possible in these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…23 These findings were confirmed by other authors. 47,48 Kobayashi et al, in a retrospective study on 137 limbs in 123 CLTI patients with lesions in both the anterior and the posterior tibial arteries, compared clinical outcomes in single versus dual tibial arteries endovascular treatment. They found that in the group of double tibial arteries treatment, the wound healing rate was significantly higher, the time to wound healing was shorter, and the repeat peripheral vascular intervention rate was lower.…”
Section: Single or Multivessel Infrapopliteal Revascularization: Whatmentioning
confidence: 99%
“…51,52 On the other hand, despite the potential benefit of achieving a complete revascularization, it is suspected that the procedure may carry a higher risk of renal impairment due the use of a greater contrast volume, longer procedure time, radiation exposure, and potential complications. 47,48,51 The GVGs assert that multivessel (tibial) revascularization may be reasonable in selected patients with advanced limb-threatening lesions (eg, WIfI stages 3 and 4) undergoing endovascular therapy if it can be safely accomplished without risking loss of a bypass target or compromising runoff to the foot. 14…”
Section: Single or Multivessel Infrapopliteal Revascularization: Whatmentioning
confidence: 99%
“…In this case report, the patient had prior peripheral arterial occlusive disease and was admitted via the emergency room with critical limb ischemia at high risk of limb loss, and underwent endovascular treatment with recanalization of femoropopliteal and peroneal arteries. 22 The worsening of the ulcer on the left external malleolus and the severity of the patient’s clinical condition may be related to those thrombotic events. However, no further investigations regarding thromboembolic events were conducted due to multiple organ failure and the severity of the patient’s clinical condition, caused by SARS-Cov-2 complications.…”
Section: Discussionmentioning
confidence: 99%